A Paleomagnetic Inspection of the Paleocene-Eocene Thermal Maximum (PETM) in the Southern Pyrenees - Oliva-Urcia, Belén; Gil-Peña, Inmaculada; Samsó, José M.; Soto, Ruth; Rosales, Idoia (Frontiers in Earth Science, 2018)
Rock magnetic properties can be useful determining paleonvironmental changes. A dramatic climate change as occurred in the PETM modified the environment and hence the magnetic properties recorded in the sediments. New paleomagnetic data from the marine record of the PETM in the Southern Pyrenean Zone shows the variation on the magnetic parameters in four different sections. The magnetic signal reveals a positive excursion of magnetic values starting before the onset of the marly interval of La Faja de las Flores Mb (beginning of the PETM record, Ilerdian) in the Carriata section with a maximum value in the marly interval. A similar magnetic signal is observed in Bujaruelo section (~10 km south of Carriata at PETM times) directly related to the marly interval of Faja de las Flores Mb. However more to the south, the PETM interval does not appear in the sedimentary record, therefore in the southern Gallisué section no magnetic excursion occurs, and in the southernmost studied Entremón section a magnetic positive excursion occurs in a thin marly interval unrelated to the PETM, and in two lower intervals of the column. All sections were subjected to later deformation during the pyrenean orogeny and the three northernmost are in the regional cleavage front where pressure-solution and remagnetizations have been described. A postfolding remagnetization component is found in the three northern sections.